Intercellular crosstalk mediated by tunneling nanotubes between central nervous system cells. What we need to advance - Capobianco, D. L.; Simone, L.; Svelto, M.; Pisani, F. (Frontiers in Physiology, 2023)
Long-range intercellular communication between Central Nervous System (CNS) cells is an essential process for preserving CNS homeostasis. Paracrine signaling, extracellular vesicles, neurotransmitters and synapses are well-known mechanisms involved. A new form of intercellular crosstalk mechanism based on Tunneling Nanotubes (TNTs), suggests a new way to understand how neural cells interact with each other in controlling CNS functions. TNTs are long intercellular bridges that allow the intercellular transfer of cargoes and signals from one cell to another contributing to the control of tissue functionality. CNS cells communicate with each other via TNTs, through which ions, organelles and other signals are exchanged. Unfortunately, almost all these results were obtained through 2D in-vitro models, and fundamental mechanisms underlying TNTs-formation still remain elusive. Consequently, many questions remain open, and TNTs role in CNS remains largely unknown. In this review, we briefly discuss the state of the art regarding TNTs identification and function. We highlight the gaps in the knowledge of TNTs and discuss what is needed to accelerate TNTs-research in CNS-physiology. To this end, it is necessary to: 1) Develop an ad-hoc TNTs-imaging and software-assisted processing tool to improve TNTs-identification and quantification, 2) Identify specific molecular pathways involved into TNTs-formation, 3) Use in-vitro 3D-CNS and animal models to investigate TNTs-role in a more physiological context pushing the limit of live-microscopy techniques. Although there are still many steps to be taken, we believe that the study of TNTs is a new and fascinating frontier that could significantly contribute to deciphering CNS physiology.